Relationship of Serum Bicarbonate Levels with 1-Year Graft Function in Kidney Transplant Recipients in Switzerland - Anna Wiegand; Nicole Graf; Marco Bonani; Diana Frey; Rudolf P. Wüthrich; Nilufar Mohebbi (Karger Publishers, 2019)
Background: Metabolic acidosis (MA) is common in kidney transplant recipients (KTRs). Several studies have shown that MA is involved in the progression of chronic kidney disease. However, it is unclear if there is also a relationship between serum bicarbonate and graft function after kidney transplantation (KTx). We hypothesized that low serum bicarbonate is associated with a lower estimated glomerular filtration rate (eGFR) 1 year after KTx. Methods: We performed a post hoc analysis of a single-center, open-label randomized trial in 90 KTRs and investigated the relationship of serum bicarbonate and graft function in the first year after KTx. Results: Prevalence of MA was high after KTx (63%) and decreased to 28% after 1 year. Bicarbonate (20.6 ± 3.0 to 22.7 ± 2.7 mmol/L) increased in the first year after transplantation whereas eGFR (53.4 ± 15.8 to 56.9 ± 18.5 mL/min/1.73 m2) did not change significantly. Higher serum bicarbonate (p = 0.029) was associated with higher eGFR in the first year after KTx. Conclusion: Prevalence of MA is high in KTRs. In the first year after KTx, serum bicarbonate was positively correlated with eGFR, suggesting a potential role of MA in kidney graft function.